Induction of Protective Immunity by a Single Low Dose of a Master Cell Bank cGMP-rBCG-P Vaccine Against the Human Metapneumovirus in Mice - Soto, Jorge A.; Gálvez, Nicolás M. S.; Pacheco, Gaspar A.; Canedo-Marroquín, Gisela; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Cellular and Infection Microbiology, 2021)
Human metapneumovirus (hMPV) is an emergent virus, which mainly infects the upper and lower respiratory tract epithelium. This pathogen is responsible for a significant portion of hospitalizations due to bronchitis and pneumonia in infants and the elderly worldwide. hMPV infection induces a pro-inflammatory immune response upon infection of the host, which is not adequate for the clearance of this pathogen. The lack of knowledge regarding the different molecular mechanisms of infection of this virus has delayed the licensing of effective treatments or vaccines. As part of this work, we evaluated whether a single and low dose of a recombinant Mycobacterium bovis Bacillus Calmette-Guérin (BCG) expressing the phosphoprotein of hMPV (rBCG-P) can induce a protective immune response in mice. Immunization with the rBCG-P significantly decreased neutrophil counts and viral loads in the lungs of infected mice at different time points. This immune response was also associated with a modulated infiltration of innate cells into the lungs, such as interstitial macrophages (IM) and alveolar macrophages (AM), activated CD4+ and CD8+ T cells, and changes in the population of differentiated subsets of B cells, such as marginal zone B cells and plasma cells. The humoral immune response induced by the rBCG-P led to an early and robust IgA response and a late and constant IgG response. Finally, we determined that the transfer of cells or sera from immunized and infected mice to naïve mice promoted an efficient viral clearance. Therefore, a single and low dose of rBCG-P can protect mice from the disease caused by hMPV, and this vaccine could be a promising candidate for future clinical trials.